Distinct effects and mechanisms of AO occurring with eastern and central Pacific El Niño on precipitation in South China during boreal winter - Y F Lan; Q Zheng; L Zhou; M Meng (Environmental Research Letters)
Eastern and central Pacific-El Niño (EP-El Niño–CP-El Niño) tend to cause distinct precipitation anomalies at low latitudes in East Asia, but their impacts in conjunction with the Arctic Oscillation (AO) at high latitudes remain largely unexplored. In this study, we analyzed the joint impacts of AO plus EP-El Niño or CP-El Niño on precipitation in South China spanning boreal winter from 1961 to 2019. We found that AO and El Niño regulated precipitation over the target region via independent teleconnection pathways. The positive/negative phase of AO can induce an anomalous cyclone/anticyclone in the Indo-Myanmar by initiating a Rossby wave from the North Atlantic, passing through the Mediterranean, Middle East, and then eastward along the subtropical jet stream to the low latitudes of East Asia. This can enhance/weaken the local Indo-Myanmar Trough, and further contribute to above/below-normal precipitation to 100° E–110° E in South China via a stronger/weaker water vapor transport and ascending/descending motion. Through a Gill-type response and/or weaker-than-normal Walker circulation, El Niño generates an anomalous anticyclone over the northwestern Pacific Ocean; specifically, CP-El Niño forces the anomalous anticyclone in the Philippines, and southerly winds on the western flank of the anticyclone can carry moisture to the area between 110° E and 120° E. However, during EP-El Niño, this anomalous anticyclone is active to the east of 130° E, which is unfavorable for precipitation in South China.